Theoretical Bases of Identifying Determinants of Protection Intentions towards Bring-Your-Own-Device (BYOD) Protection Behaviors - Al-Harthy I.M.; Rahim F.A.; Ali N.; Singun A.P. (Institute of Electrical and Electronics Engineers Inc., 2023)
Access control; Computation theory; Data privacy; Bring your own devices; Business organizations; Personal devices; Privacy and security; Privacy violation; Security breaches; Sensitive informations; Unauthorized access; Intelligent computing